2012
DOI: 10.1021/ja305180n
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the BfrB–Bfd Complex Reveals Protein–Protein Interactions Enabling Iron Release from Bacterioferritin

Abstract: Ferritin-like molecules are unique to cellular iron homeostasis because they can store iron at concentrations much higher than those dictated by the solubility of Fe 3+ . Very little is known about the protein interactions that deliver iron for storage or promote the mobilization of stored iron from ferritinlike molecules. Here, we report the X-ray crystal structure of Pseudomonas aeruginosa bacterioferritin (Pa-BfrB) in complex with bacterioferritin-associated ferredoxin (Pa-Bfd) at 2.0 Å resolution. As the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(157 citation statements)
references
References 57 publications
4
153
0
Order By: Relevance
“…To completely understand the participation of apo-Bfd in the release of iron, apo-Bfd was prepared and isolated in a subsequent study. 110 As expected, the apo-protein shows only a 280 nm band (red in Figure 17(B)), which differs from the spectrum of holo Pa Bfd (black trace) in that peaks at 334 nm, 424 nm, and 465 nm characteristic of an iron sulfur cluster are missing. The influence of apoBfd on iron release from Pa BfrB was then probed by addition of NADPH to a mixture of Pa BfrB, Pa FPR, and apo-Bfd in concentrations very similar to those used to study the effect of Pa Bfd.…”
Section: B Iron Release From Pa Bfrb Requires Pa Bfd To Mediate Elecsupporting
confidence: 57%
See 1 more Smart Citation
“…To completely understand the participation of apo-Bfd in the release of iron, apo-Bfd was prepared and isolated in a subsequent study. 110 As expected, the apo-protein shows only a 280 nm band (red in Figure 17(B)), which differs from the spectrum of holo Pa Bfd (black trace) in that peaks at 334 nm, 424 nm, and 465 nm characteristic of an iron sulfur cluster are missing. The influence of apoBfd on iron release from Pa BfrB was then probed by addition of NADPH to a mixture of Pa BfrB, Pa FPR, and apo-Bfd in concentrations very similar to those used to study the effect of Pa Bfd.…”
Section: B Iron Release From Pa Bfrb Requires Pa Bfd To Mediate Elecsupporting
confidence: 57%
“…To distinguish between these possibilities, the conditions resulting from preparing apo-Bfd in situ were emulated in a solution containing apo-Bfd, Pa BfrB, Pa FPR, Fe 2+ , S 2− , and bipy. 110 Addition of NADPH to this solution promotes iron release from Pa BfrB (black plot in Figure 17(C)). In contrast, iron release from a solution containing Pa BfrB, Pa FPR, Fe 2+ , S 2− , and bipy, but lacking apo-Bfd is inefficient (red in Figure 17(C)).…”
Section: B Iron Release From Pa Bfrb Requires Pa Bfd To Mediate Elecmentioning
confidence: 99%
“…10). Recent theoretical studies [82] and experimental observations [138] commented above give nowadays further support to this proposal. The interaction of ferritin with multiple biomolecules, not strictly metalloproteins, has also been reported in the literature.…”
Section: Section 5)mentioning
confidence: 61%
“…202 A recent X-ray crystallography study using Pseudomonas aeroginosa bacterioferritin (PaBFR) showed that PaBfd associates with the bacterioferritin surface at the 2-fold symmetry axis on the top of the heme group ( Figure 17). 203 As a result, the edge-to-edge distance between the [2Fe-2S] cluster in PaBfd and the heme group in PaBFR is ca. 18 Å, suggesting long distance electron transfer 204 (Figure 17).…”
Section: Iron Release In Bacterioferritinmentioning
confidence: 99%